The Influence of Communication Factors, Work Experience and Job Training on Employee Productivity at the Karya Darma Makassar College Foundation - Halijah Nur (Cita konsultindo, 2024)
This research uses a quantitative approach, namely an approach that emphasizes analysis of numerical data processed using statistical methods. Quantitative research is a type of research that produces discoveries that can be achieved (obtained) using statistical procedures or other means of quantification (measurement). In a quantitative approach, the nature of the relationship between variables is analyzed using objective theory. This research is associative research, namely research that aims to determine the relationship or influence between two or more variables. (Sugiyono, 2010). The subjects in this research were employees of the Karya Dharma Makassar College Foundation. Relations between employees can also be improved by giving feedback to one employee and another. Feedback is very useful for knowing strengths and weaknesses during the work process. A job can be said to be effective, if with certain sacrifices it can provide maximum results both in terms of quality and number of units of output. So maximum results in every job depend on effective working methods, thanks to effective communication efforts made by leaders with employees to achieve maximum results. The Influence of Work Experience on Productivity. By providing planned training from the company, employees will be trained to solve the problems they face in carrying out their work so that their work productivity will increase.